Evaluation of Blue Gene/Q hardware support for transactional memories - Amy Wang; Gaudet, Matthew; Wu, Peng; Amaral, Jose Nelson; Ohmacht, Martin; Barton, Christopher; Silvera, Raul; Michael, Maged (PACT'12 : proceedings of the 21st International Conference on Parallel Architectures and Compilation Techniques, September 19-23, Minneapolis, Minnesota, USA, 2012)
This paper describes an end-to-end system implementation of the transactional memory (TM) programming model on top of the hardware transactional memory (HTM) of the Blue Gene/Q (BG/Q) machine. The TM programming model supports most C/C++ programming constructs on top of a best-effort HTM with the help of a complete software stack including the compiler, the kernel, and the TM runtime. An extensive evaluation of the STAMP benchmarks on BG/Q is the first of its kind in understanding characteristics of running coarse-grained TM workloads on HTMs. The study reveals several interesting insights on the overhead and the scalability of BG/Q HTM with respect to sequential execution, coarse-grain locking, and software TM.